613 Congenital Diaphragmatic Hernia Surveillance in Ireland. (October 2012) - Chukwu, J; Molloy, EJ
Abstract : Introduction: The incidence of Congenital Diaphragmatic Hernia (CDH) varies from 1 in 2, 000 to 15, 000 births per annum. Due to the legislation prohibiting termination of any pregnancy in the Republic of Ireland (ROI) we hypothesised that the incidence would be different to international reports. There is no mandatory reporting of CDH cases in the ROI and Northern Ireland (NI). Aims: To determine the true incidence of CDH in the ROI and NI. Methods: Reporting of CDH cases to the Irish Paediatric Surveillance Unit (IPSU) based in Dublin started in January 2010. Doctors reported new cases to IPSU using the pro-forma provided. Details of the reported cases were collected using a detailed CDH questionnaire. Results: 23 cases were reported to the IPSU within the 2 year period consisting of 10 cases in 2010 and 13 in 2011; 8 cases from NI and 15 cases from ROI. The incidence rate in the 2 years using IPSU figures was 0.12 per 1000 live births per annum. The questionnaire was completed in 12 cases. 11/12(92%) made it to the surgical centres. However the Hospital in Patient System record in one of the three surgical centres indicated that only 6/15(40%) cases managed in that centre in the 2-year period were reported to IPSU. Conclusion: It was difficult to determine the true incidence of CDH using the IPSU data due under-reporting. Increased reporting may be achieved by raising awareness and by the use of capture-recapture mechanism. The establishment of a national congenital anomaly register is also indicated.